Understanding of teaching and its manifestation among excellent educators in a selected public university - Abdullah, Hasnah; Abd. Aziz, Noor Azam (2007)
The research was conducted to explore the understanding of teaching of excellent educators in a selected public university. Three research questions guided the study; first, what do educators believe to be the purposes of education?, second, what facilitated the understanding of teaching development?, and third, how is the understanding of teaching adhered to, manifested in their teaching practice? The study employed qualitative multiple case study approach to answer the research questions. The primary data were collected through in depth interviews and the secondary data were collected through observations in the classroom, laboratory and discussion sessions after lectures. The analyses of this study were done through within-case analysis and cross-case analysis explained the findings from the four excellent educators. The study discovered that the purposes of education were for change, transmitting knowledge, and character building. Respondents’ background as well as understanding of learning and teaching concepts had contributed to the development of the understanding of teaching. The adhered understanding was manifested in their teaching. These can be observed through their preparation and openness to assists students. Their teaching roles as experts and organizers were reflected in their teaching. They have been a major source of reference for their students as well as the society at large.